Exploring mid-level bureaucracy: a tentative typology - Cavalcante, Pedro L.C.; Lotta, Gabriela S.; Yamada, Erika M.K. (Revista Brasileira de Ciência Política, 2018)
The paper’s main goal is to present an original typology of bureaucrats, situated in intermediate layer of the civil service structure. This specifc set of players, the mid-level bureaucrat (MLB), is seen as a strategic group, primarily, because of its connection role and position between the top ofcials and the policy executors. Despite their relevance and well-known heterogeneity, few studies have explored this diversity and the eï¬€ects in the policymaking. In order to fulfll this gap and deepen the understanding of the MLBs, this article proposes a typology that includes crucial dimensions, such as profle, background and performance, and, thus, empirically confrms the heterogeneity assumption in the Brazilian federal civil service.